Remarks on the Study of the Electronic Properties and Photoionization Process in Rotating 2D Quantum Rings - Carlos Magno O. Pereira; Frankbelson dos S. Azevedo; Edilberto O. Silva (Quantum Reports)
The electronic and optical properties of a mesoscopic heterostructure of a two-dimensional quantum ring composed of Gallium Arsenide (GaAs) semiconductors are investigated. Using the confinement potential proposed by Tan and Inkson to describe the system under analysis, we conducted a numerical study of the photoionization cross-section for a 2D quantum ring with and without rotation effects. The interior of the quantum ring is traversed by an Aharonov–Bohm (AB) flux. Our research aims to investigate how this mesoscopic structure’s electronic and optical properties respond to variations in the following parameters: average radius, AB flux, angular velocity, and incident photon energy. Under these conditions, we establish that optical transitions occur from the ground state to the next excited state in the conduction subband, following a specific selection rule. One of the fundamental objectives of this study is to analyze how these rules can influence the general properties of two-dimensional quantum rings. To clarify the influence of rotation on the photoionization process within the system, we offer findings that illuminate the effects of the pertinent physical parameters within the described model. We emphasize that, although this is a review, it provides critical commentary, analysis, and new perspectives on existing research. Some results presented in this paper can be compared with those in the literature; however, new physical parameters and quantum ring configurations are used.